Skeletal muscle phenotypic switching in heart failure with preserved ejection fraction - Saw, Eng Leng; Werner, Louis Dominic; Zamani, Payman; Chirinos, Julio A.; Valero-Muñoz, María; Sam, Flora (Frontiers in Cardiovascular Medicine, 2022)
Background Skeletal muscle (SkM) phenotypic switching is associated with exercise intolerance in heart failure with preserved ejection fraction (HFpEF). Patients with HFpEF have decreased type-1 oxidative fibers and mitochondrial dysfunction, indicative of impaired oxidative capacity. The SAUNA (SAlty drinking water/Unilateral Nephrectomy/Aldosterone) mice are commonly used in HFpEF pre-clinical studies and demonstrate cardiac, lung, kidney, and white adipose tissue impairments. However, the SkM (specifically the oxidative-predominant, soleus muscle) has not been described in this preclinical HFpEF model. We sought to characterize the soleus skeletal muscle in the HFpEF SAUNA mice and investigate its translational potential. Methods HFpEF was induced in mice by uninephrectomy, d-aldosterone or saline (Sham) infusion by osmotic pump implantation, and 1% NaCl drinking water was given for 4 weeks. Mice were euthanized, and the oxidative-predominant soleus muscle was collected. We examined fiber composition, fiber cross-sectional area, capillary density, and fibrosis. Molecular analyses were also performed. To investigate the clinical relevance of this model, the oxidative-predominant, vastus lateralis muscle from patients with HFpEF was biopsied and examined for molecular changes in mitochondrial oxidative phosphorylation, vasculature, fibrosis, and inflammation. Results Histological analyses demonstrated a reduction in the abundance of oxidative fibers, type-2A fiber atrophy, decreased capillary density, and increased fibrotic area in the soleus muscle of HFpEF mice compared to Sham. Expression of targets of interest such as a reduction in mitochondrial oxidative-phosphorylation genes, increased VEGF-α and an elevated inflammatory response was also seen. The histological and molecular changes in HFpEF mice are consistent and comparable with changes seen in the oxidative-predominant SkM of patients with HFpEF. Conclusion The HFpEF SAUNA model recapitulates the SkM phenotypic switching seen in HFpEF patients. This model is suitable and relevant to study SkM phenotypic switching in HFpEF.